GAMBARAN GAYA BELAJAR ANAK USIA 5-6 TAHUN DI RA. JANNATUL ILMI KECAMATAN TAMPAN PEKANBARU - Risma, Devi; ', Suryati; ', Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research constive descriptive, This descriptive research aim is toknow the description of child’s learning style at 5 – 6 years old in RA Jannatul IlmiTampan Pekanbaru. The sample is al the children at 5 – 6 years old in RA Jannatul IlmiTampan Pekanbaru 20 children. The data collection technique is observation sheetthere is a statement about child’s learning style in early age. Based on the result, it canconclude that child’s learning style at 5 – 6 years old in RA Jannatul Ilmi is good level(65,72%), meanwhile based on each indicator visual learning style is good level(78,89%), auditory learning style is good level (75,55%), on kinesthetic is good level(72%), meanwhile on the multisensory learning style is good enough (58,14%). It meansthat basically is not all the children have been applied on their own learning style.Keywords: learning Style